Spicoid ontogeny in Diplasia (Mapanioideae, Cyperaceae): an approach on the developmental processes operating in Mapanioideae spicoids - Monteiro, Mariana Maciel (2020)
Mapanioideae (besides Cyperoideae the other subfamily of Cyperaceae) is divided in two tribes (Hypolytreae and Chrysitricheae) in which the reproductive units (spicoids) are interpreted either as flowers or as inflorescences. Little is known about the ontogenetic factors operating during the spicoid development and how they may contribute to the spicoid final morphology. In this context, we studied the spicoid development in the monotypic genus Diplasia and compared it with other developmental studies in Mapanioideae. Our results show that the main developmental variations are related to the sequence of organ formation, the size and shape of the spicoid primordium and the influence of the subtending bract constraints in different sides of such primordium. Our hypotheses to explain the spicoid’s morphological variation in Mapanioideae are: that size and shape of the spicoid primordium contribute to changes in the number and position of organs to be formed, and spatial constraints of the subtending bracts influence the reduction of adaxial parts. Developmental features of the spicoids showed to be stable within the tribe. Our observations of the nature of spicoids in Diplasia give arguments for both, floral and inflorescence interpretations, sustaining the uncertainty towards a satisfactory definition. The difficulty in distinguishing the boundaries of flower and inflorescence nature in the spicoids raised a third hypothesis where the spicoid could be interpreted as a de novo structure, due to a reorganisation of regulatory genes resulting in a single unit with flower and inflorescence features combined, considered a synapomorphy of Mapanioideae.